Prevalence of low back pain in handcrafters - Putu Aristya Crisanty; Anak Agung Gede Eka Septian Utama; Anak Ayu Nyoman Trisna Narta Dewi; Ni Wayan Tianing (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: Low back pain is a musculoskeletal disorder caused by incorrect ergonomic conditions at work. It is located at the inferior gluteal fold and the coastal border and lasts more than 24 hours. This study aimed to determine the prevalence of low back pain complaints in handcrafters. Methods: This research used an observational analytic design with a cross-sectional approach. The sampling technique used was purposive sampling. The inclusion criteria for this study were handcrafters of serati banten aged 45-55. In contrast, the exclusion criteria were injuries in the lower back region. The total number of respondents who participated in this study was 50 people. The research location was in Gianyar, Bali. Data was collected from January to October 2023. Data were collected by measuring VAS and REBA. VAS measured the severity and relief of pain, while the REBA questionnaire analyzed work posture. Results: The results of research regarding the prevalence of low back pain in handcrafters of serati banten in Gianyar Regency based on internal factors showed the majority experienced low back pain of mild intensity (60%), and external factors showed that the majority of pain incidents occurred in respondents with a working period of >5 years (52%), working in a sitting position (56%) with moderate risk working postures (64%). Conclusion: The frequency of low back pain occurrences due to external factors was dominated by respondents with less than five years of working experience who worked in a sitting position with a medium-risk work posture.